Mallarmé's 'Livre': notes towards a schizotheatre. Issue 1 (2nd January 2019) - Gotman, Kélina
ABSTRACT: Stéphane Mallarmé's 'Livre' constitutes a set of notes towards a performance project that was never realised. This essay reads these notes as schizotheatre: a theatre of crisis in which the poet, as Orchestrator, sits at the centre of a web of processes and procedures designed at once to obliterate him and enable a series of audience and performer connections. Mallarmé experienced a spiritual crisis in the late 1860s, leading to his depersonalisation and derealisation, as well as his belief that he was in the midst of construing a Grand Oeuvre or great work. The Livre was to be the culmination of this, at once an impossible and, as this essay shows, an intensely pragmatic project. While Mallarmé's work has been widely celebrated in poetry and to a lesser extent in music, this essay seeks to reposition him at the vanguard of what I call a choreographic textual practice, in which the mise en scène of language fragments on the page constitute a 'reading' dance.